THE Decision Support System in District Cooling System (DCS) Installation - MICHAEL, ESTHER (Progress in Engineering Application and Technology, 2022)
District Cooling System (DCS) is consistent, profitable and effective system intentionally used on district growth that encounters climate changes cause by nature loads and development. This study emphasizes on design consideration for existing building to install DCS focused on building capability, urban planning and thermal prediction. Design consideration to install DCS and the characteristic required to install DCS in existing building area. Thematic analysis has been used in this study based on articles and pass research from year 2004 to 2021. The results conclude by the characteristic category DCS plant location, energy resources, economic city stage and type of building design compatibility. Result from the study shown that most DCS area located near to sea and the economic was in development phase area. Furthermore, the type of existing building need to be Multi-Energy System (MES) to install the DCS system.